Efficiency Wages and Labor Mobility in an Open Economy - Santaella, Julio (IMF Working Papers; Working Paper ;, 1993)
The paper analyzes the role of labor market segmentation and relative wage rigidity in the transmission process of macroeconomic shocks in a two-sector optimizing model of a small open economy. The analysis is first conducted in the context of perfect intersectoral labor mobility. The discussion is then extended to consider the existence of short-run constraints on labor movements. The results highlight the role of efficiency considerations in the behavior of sectoral wages. A deflationary policy induces a reallocation of labor across sectors, but has no long-run effect on the unemployment rate.